PENGARUH SENAM HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH LANSIA - Islah S, Nurul; Djabo Buton, La (Literasi Intelektual, 2025)
Background: Diabetes mellitus is a chronic disease that requires lifelong treatment and can affect the patient's quality of life. Social support from family and the environment as well as self-efficacy have an important role in disease management and improving quality of life Objective: This study aims to analyze the relationship between support system and self-efficacy and the quality of life of patients with diabetes mellitus at the Perumnas Health Center. Methods: The study used a quantitative method with a cross-sectional design on 53 respondents selected through purposive sampling. The research instruments were in the form of a questionnaire support system, self-efficacy, and quality of life, with data analysis using the Chi-Square test. Results: The results showed that there was a significant relationship between support system and quality of life (p = 0.007) and between self-efficacy and quality of life (p = 0.001). Conclusion: It is concluded that the better the social support and the higher the self-efficacy, the better the quality of life of patients with diabetes mellitus. Health workers and families are expected to increase support and provide motivation to strengthen patients' self-confidence in managing their illnesses.